Preparation method of mineralized collagen scaffold material with bionic structure, mineralized collagen scaffold material and application of mineralized collagen scaffold material
By preparing norepinephrine-mineralized collagen scaffold material with bionic structure, the shortcomings of existing bone tissue repair materials in terms of biocompatibility, mechanical strength and immune response are solved, and efficient repair of bone tissue defects is achieved.
Patent Information
- Application Number
- CN202411606848.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-12
AI Technical Summary
Existing bone tissue repair materials have shortcomings in biocompatibility, mechanical strength and immune response, which are difficult to meet clinical needs.
By preparing polyacrylic acid-stabilized amorphous calcium phosphate solution and norepinephrine-containing collagen solution, isoelectric focusing and stretching techniques are used to prepare collagen membranes with bionic structures, and norepinephrine-mineralized collagen is obtained by freeze-drying Stent material.
This material has excellent biocompatibility, osteogenesis induction and mechanical strength, which can effectively promote bone tissue defect repair, and has high biological activity and bone-promoting tissue repair ability.
Smart Images

Figure CN119455110A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of biomedical engineering, and particularly relates to a preparation method of a mineralized collagen scaffold material with a bionic structure, the mineralized collagen scaffold material and applications thereof. Background Art
[0002] As the most important hard tissue in the human body, bone plays a supporting and protective role. Bone tissue defects caused by sports, traffic accidents, diseases, etc. are common clinical diseases, which endanger the health of patients and bring great pain to patients. At present, the main methods of bone tissue repair are implantation of autologous bone transplants, allogeneic bone transplants, xenogeneic bone transplants or synthetic artificial bones. Autologous bone has the dual effects of osteoinduction and osteoconduction, and has been clinically proven to be an effective means of bone repair. However, its application is limited due to the lack of donor tissue and additional secondary defects. At the same time, immune rejection or disease transmission caused by allogeneic bone transplants and xenogeneic bone transplants brings a high risk of pain or infection to patients. Low temperature treatment can reduce the occurrence of immune rejection reactions, but its mechanical strength and osteoinductivity will be reduced accordingly. Therefore, it is of great significance to develop bone tissue defect repair materials with good performance.
[0003] Ideal bone tissue repair materials should have good osteoconductivity, biocompatibility, absorbability and sufficient mechanical strength. At present, commonly used bone repair materials include metal materials, ceramic implants and polymer scaffold materials. The most commonly used metal material in clinical practice is titanium alloy. Titanium is non-toxic and harmless, has good corrosion resistance, and its elastic modulus is close to that of human hard tissue. However, the surface of titanium alloy is relatively smooth, resulting in poor bone bonding performance. Ceramic implants are mainly calcium phosphate ceramics, including hydroxyapatite (HA) and β-tricalcium phosphate, which have been widely studied in the field of bone repair. Although they are similar to the inorganic composition in natural bone tissue, the poor fracture toughness and tensile strength of calcium phosphate ceramics limit its application in the field of biomaterials. Polymeric scaffold materials can be compounded with growth factors to accelerate bone repair, but the osteoconductivity of most polymers is weak. Summary of the invention
[0004] In order to obtain a bone tissue defect repair material with good performance, the present invention provides a method for preparing a mineralized collagen scaffold material with a bionic structure. The mineralized collagen scaffold material prepared by the method has excellent biocompatibility, osteogenic inductivity and sufficient mechanical strength, can effectively promote bone tissue defect repair, and has good application prospects in the field of bone tissue engineering.
[0005] The invention also provides a mineralized collagen scaffold material with a bionic structure and application thereof.
[0006] The present invention is achieved through the following technical solutions:
[0007] The present invention provides a method for preparing a mineralized collagen scaffold material with a biomimetic structure, the preparation method comprising:
[0008] preparing an amorphous calcium phosphate solution stabilized by polyacrylic acid, wherein the molar ratio of the Ca element to the P element in the amorphous calcium phosphate solution is 1.67:1;
[0009] Prepare a collagen solution containing norepinephrine;
[0010] The collagen solution is subjected to isoelectric focusing treatment at a constant voltage to form a dense membrane, and then the dense membrane is stretched to produce a deformation of 120% to 200%, thereby obtaining a collagen membrane with a bionic structure;
[0011] The collagen membrane is immersed in the amorphous calcium phosphate solution and then freeze-dried to obtain a norepinephrine-mineralized collagen scaffold material.
[0012] Furthermore, in the amorphous calcium phosphate solution, the concentration of polyacrylic acid is 1-2 mg / mL, the concentration of calcium ions is 0.025-0.1 mol / L, and the concentration of phosphate ions is 0.015-0.06 mol / L.
[0013] Furthermore, the preparation of the amorphous calcium phosphate solution stabilized by polyacrylic acid specifically comprises:
[0014] Dissolve polyacrylic acid in water, then add CaCl2 to obtain a mixed solution;
[0015] K2HPO4 solution was added dropwise to the mixed solution, and then NaOH was added to adjust the pH to 9.5±0.2 to obtain an amorphous calcium phosphate solution stabilized by polyacrylic acid.
[0016] Furthermore, in the collagen solution, the concentration of collagen is 0.5-1 mg / mL, and the mass ratio of the collagen to the norepinephrine is 100:(0.5-5).
[0017] Preferably, the collagen includes any one of bovine collagen, porcine collagen and fish skin collagen.
[0018] Further, the collagen solution is subjected to isoelectric focusing treatment at a constant voltage to form a dense membrane, and then the dense membrane is stretched to produce a 120% to 200% deformation to obtain a collagen membrane with a bionic structure, specifically comprising:
[0019] The collagen solution is subjected to isoelectric focusing treatment for 10 to 20 minutes at a constant voltage of 10 to 20 V to form a dense membrane, and then the dense membrane is stretched at a speed of 1 to 3 mm / min to produce a deformation of 120% to 200%, thereby obtaining a collagen membrane with a bionic structure.
[0020] Furthermore, the collagen membrane is immersed in the amorphous calcium phosphate solution and then freeze-dried to obtain a norepinephrine-mineralized collagen scaffold material, which specifically includes:
[0021] The collagen membrane is immersed in the amorphous calcium phosphate solution at 37±1° C. for 12±2 hours, and then freeze-dried to obtain a norepinephrine-mineralized collagen scaffold material.
[0022] Based on the same inventive concept, the present invention provides a mineralized collagen scaffold material with a bionic structure, and the mineralized collagen scaffold material is prepared by the above-mentioned method for preparing a mineralized collagen scaffold material with a bionic structure.
[0023] Based on the same inventive concept, the present invention provides an application of a mineralized collagen scaffold material with a bionic structure as or in the preparation of a bone defect repair material.
[0024] Based on the same inventive concept, the present invention provides a bone defect repair material, wherein the bone defect repair material comprises the above-mentioned mineralized collagen scaffold material with a bionic structure;
[0025] Alternatively, the raw material for preparing the bone defect repair material comprises the above-mentioned mineralized collagen scaffold material with a bionic structure.
[0026] One or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:
[0027] 1. The present invention discloses a method for preparing a mineralized collagen scaffold material with a biomimetic structure. The method comprises adding an appropriate amount of norepinephrine (NE) to a collagen solution, preparing a collagen film with a biomimetic structure by an isoelectric focusing method, immersing the collagen film in an amorphous calcium phosphate solution stabilized by polyacrylic acid (PAA) for mineralization, and obtaining a norepinephrine-mineralized collagen scaffold after freeze drying. The scaffold material constructed by the present invention can be used in a bone defect repair system, can regulate the two-phase ratio and mechanical strength of the micro-scaffold according to different amorphous calcium phosphate solution concentrations, has high biological activity, promotes bone tissue repair ability and promotes nerve repair ability, and can be applied to biomedical fields such as drug controlled release systems and bone defect treatment.
[0028] 2. The present invention provides a method for preparing a mineralized collagen scaffold material with a bionic structure. The method uses collagen as a scaffold substrate, and uses an isoelectric focusing method to align collagen fibers. In the process, norepinephrine is added to allow it to enter the internal structure of the material, and then it is soaked in an amorphous calcium phosphate solution at 37° C. The amorphous calcium phosphate solution is a CaCl2 and K2HPO4 solution stabilized by PAA, and the Ca:P ratio is 1.67. Various functional groups on the surface of collagen are combined with calcium phosphate salts to form a hydroxyapatite (HA) mineral layer to enhance the mechanical properties and biological properties of the collagen scaffold. Finally, the collagen scaffold loaded with norepinephrine is obtained by freeze drying. Norepinephrine has an anisotropic mineralized collagen scaffold with a structure similar to natural hard bone. This method starts from the perspective of material structure and uses collagen and hydroxyapatite to simulate the highly arranged, anisotropic fine structure of natural bone in vitro, so that the material obtains functions and properties similar to natural bone tissue. The addition of norepinephrine enhances the material's ability to promote bone regeneration from the perspective of promoting nerve growth, and can be applied to bone tissue engineering. The preparation process is simple and easy, the conditions are mild, the production cycle is short, and it is non-toxic and harmless to organisms. It provides rich theoretical guidance and technical basis for the design and development of bionic scaffolds, and has great application value in the biomedical field.
[0029] 3. The present invention provides a mineralized collagen scaffold material with a biomimetic structure. The material has a highly arranged, anisotropic structure, which enhances the mechanical properties and structural stability of the scaffold. Collagen has good biocompatibility and low antigenicity. The HA formed by surface mineralization synergistically enhances the biological properties of the material, can promote the attachment and growth of bone marrow mesenchymal stem cells (BMSC) and can provide a favorable environment for the formation of new bone tissue. In addition, the mineralized HA has excellent biocompatibility and osteogenic induction, has the function of promoting osteogenesis and blood vessel growth, and can be used for repairing hard bone parts. At the same time, hydroxyapatite HA as an inorganic mineral provides a certain degree of mechanical strength for the scaffold.
[0030] 4. The present invention discloses a mineralized collagen scaffold material with a biomimetic structure. The material is prepared by adding NE to collagen at room temperature and then mineralizing it with amorphous calcium phosphate after isoelectric focusing at a voltage of 10 to 20 V. The inorganic content of the mineralized collagen surface can be regulated within a certain range by changing the concentration of the amorphous calcium phosphate solution. The material can be used to repair hard bone tissue defects and has good biocompatibility, mechanical properties and structural stability. After freeze drying, the scaffold has certain interconnected pores, which are beneficial to the exchange of nutrients, cell migration and proliferation. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0032] Figure 1 This is a scanning electron micrograph of the norepinephrine-mineralized collagen scaffold prepared in Example 1.
[0033] Figure 2 This is a tensile test diagram of the norepinephrine-mineralized collagen scaffold prepared in Example 1.
[0034] Figure 3 This is the data on the in vitro effect of the norepinephrine-mineralized collagen scaffold prepared in Example 1 on BMSC cell activity.
[0035] Figure 4 This is a CT image of the norepinephrine-mineralized collagen scaffold prepared in Example 1 acting on rat skull defect repair in vivo for 4 weeks. DETAILED DESCRIPTION
[0036] The present invention will be described in detail below in conjunction with specific implementations and examples, and the advantages and various effects of the present invention will be more clearly presented. It should be understood by those skilled in the art that these specific implementations and examples are used to illustrate the present invention, rather than to limit the present invention.
[0037] Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. In the event of a conflict, the present specification takes precedence.
[0038] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0039] The overall idea of the present invention is as follows:
[0040] Bone tissue in the adult human body accounts for about 15% of the total body weight. It is a sports organ with multiple structural levels and carries a series of biomechanical loads. With the emergence of nanoscale three-dimensional imaging technology, researchers have proposed a nine-level structure of bone. The first four levels of structure belong to the microstructure, involving the main components of bone, mineralized collagen fibrils and the arrangement of mineralized collagen fibers. The last five levels of structure belong to the macrostructure, including the type of bone (woven bone, parallel fiber bone), tissue elements (lamellar body, osteon, fibrolamellar bone), cancellous bone and compact bone. From the perspective of macrostructure, the bone structure is mainly divided into compact bone, which is located on the surface of the bone and has a hard texture and strong compressive resistance, and cancellous bone, which is located on the inner side of the bone and is interwoven by many spongy / lamellar trabeculae. Compact bone is composed of bone blocks and Haversian canals surrounding blood vessels, showing a layered structure, and a single layer is composed of orderly arranged mineralized collagen fiber bundles. Compared with compact bone, cancellous bone presents a significant porous morphological feature, and produces more cellular components on its surface, which results in the mechanical properties of cancellous bone being far inferior to compact bone. From a microscopic perspective, a characteristic basic unit of bone is mineralized collagen fibrils, the main components of which are HA and type I collagen (TypeⅠcollagen, ColⅠ). This can be described by a mineral and collagen assembly model: curved needle-shaped mineral particles merge laterally to form slightly twisted plates, forming a continuous fiber cross-phase on the surface and gaps of collagen. The inventors believe that it is precisely because of this highly arranged, anisotropic, biphasic fine structural design that bone tissue has excellent tensile strength and toughness, as well as high stiffness and compressive strength.
[0041] Norepinephrine (NE) is both a neurotransmitter, which is mainly synthesized and secreted by sympathetic postganglionic neurons and adrenergic nerve endings in the brain, and is the main neurotransmitter released by the latter. It is also a hormone, which is synthesized and secreted by the adrenal medulla, but the content is relatively small. It is reported that NE can promote the release of glial cell-derived neurotrophic factor (GDNF) from BMSCs, has a nutritional effect on normal nerve cells, and is a bioactive factor that regulates the repair function of damaged nerves, maintains the survival of sympathetic and sensory nerves, promotes the differentiation of nerve cells, and determines the extension direction of axons. In the process of bone development and regeneration, non-bone systems such as the nervous system, vascular system, and immune system play an indispensable role. Various types of nerves enter the bone and promote bone tissue regeneration by secreting various molecules and interacting with bone cell line cells (such as osteoblasts and bone marrow stromal stem cells) and other cells colonized in the bone microenvironment (such as osteoclasts and vascular endothelial cells). Despite the interdependent relationship between nerves and bones, most studies in the field of bone tissue engineering have ignored the role of the nervous system.
[0042] Based on this, the present invention proposes a mineralized collagen scaffold material with a bionic structure, which can not only improve the mechanical properties and stability of the collagen scaffold to meet the needs of bone defect treatment, but also load neurotransmitters to achieve the controlled release of trace drugs and nerve repair during bone defect treatment, so as to meet the needs of clinical bone tissue repair.
[0043] The present invention is inspired by natural bone. By simulating the structure and properties of natural bone tissue, the bionic mineralization strategy is used to improve the mechanical and biological properties of the matrix material and enhance the bone tissue repair effect of the material. Collagen and hydroxyapatite are the most abundant organic and inorganic components in natural bone, respectively. Due to their excellent biocompatibility and biodegradability, they are often used as bionic composite materials in tissue engineering. From the perspective of material structure, the present invention prepares a highly arranged, anisotropic structure similar to natural bone by isoelectric focusing. This directional arrangement enables the material to have better mechanical properties and structural stability, and its connected gaps are conducive to cell migration and proliferation. In addition, the nervous system plays an indispensable role in the bone regeneration process. The introduction of neurotransmitter NE in the bone regeneration material further improves the osteoinduction ability of the material from the perspective of nerve growth. This bionic material has a good application prospect in bone tissue engineering.
[0044] The present invention uses collagen (from bovine source - extracted from bovine Achilles tendon) as raw material. Collagen is the most abundant protein, among which type I collagen accounts for 90% of all types of collagen in the body and is mainly present in bones, bone tendons, corneas and ligaments. It has excellent biocompatibility, low antigenicity, high swelling capacity, the ability to promote cell attachment and growth and provide a favorable environment for the formation of new bone tissue, and plays a significant role in the mechanical stability and adjustability of mammalian collagen tissue. Norepinephrine belongs to catecholamine in chemical structure and is combined with collagen through CN. With the degradation of the material, it promotes BMSC to secrete bioactive factors that have a regulating effect on the repair function of damaged nerves, maintains the survival of sympathetic nerves and sensory nerves, and promotes the formation of bone repair from the perspective of nerve growth. The amorphous calcium phosphate solution used in the subsequent mineralization step can also penetrate into the collagen gap, promote the formation of collagen gap mineralization, and enhance the mechanical properties of the collagen scaffold.
[0045] The present invention also proposes a method for preparing a mineralized collagen scaffold material with a biomimetic structure, in which an amorphous calcium phosphate solution is used to mineralize the collagen scaffold, which does not produce substances harmful to the organism and improves the stability and mechanical properties of the material. Various functional groups on the surface of collagen can combine with calcium ions in the solution to form sites, promoting the formation of HA crystals. Amorphous calcium phosphate stabilized by PAA has the characteristics of mobility, positive charge, and small size, allowing minerals to penetrate into the negatively charged collagen interstitial area, forming collagen fiber interstitial mineralization to further improve the mechanical properties of the material. The prepared norepinephrine-mineralized collagen scaffold material is completely free of toxic chemicals and has high potential application value in the fields of biomineralization, bone tissue engineering, etc.
[0046] The present invention uses collagen as the main raw material to prepare the scaffold material, and the operation steps are simple, the cycle is short, the conditions are mild, and the sources are wide. The material has low toxicity risk, good stability and degradability, and also has adjustable mechanical properties. Adding norepinephrine to the material can effectively promote BMSC proliferation and nerve growth, and has great application and promotion value.
[0047] Specifically, the present invention provides a method for preparing a mineralized collagen scaffold material with a biomimetic structure, comprising:
[0048] S1. preparing an amorphous calcium phosphate solution stabilized by polyacrylic acid, wherein the molar ratio of Ca element to P element in the amorphous calcium phosphate solution is 1.67:1;
[0049] S2. preparing a collagen solution containing norepinephrine;
[0050] S3. performing isoelectric focusing treatment on the collagen solution at a constant voltage to form a dense membrane, and then stretching the dense membrane to produce a deformation of 120% to 200%, thereby obtaining a collagen membrane with a bionic structure;
[0051] S4. Soaking the collagen membrane in the amorphous calcium phosphate solution, and then freeze-drying it to obtain a norepinephrine-mineralized collagen scaffold material.
[0052] Wherein, in the amorphous calcium phosphate solution, the concentration of polyacrylic acid is 1-2 mg / mL, the concentration of calcium ions is 0.025-0.1 mol / L, and the concentration of phosphate ions is 0.015-0.06 mol / L.
[0053] In the present invention, the molar ratio of Ca element to P element in the amorphous calcium phosphate solution is 1.67:1, and the pH is adjusted to 9.5±0.2, which can promote the crystallization of calcium phosphate to form hydroxyapatite. In the amorphous calcium phosphate solution, the role of polyacrylic acid is to attract calcium ions and phosphorus ions through electrostatic force, so that calcium and phosphorus crystallization is largely restricted to form amorphous calcium phosphate clusters. Fluid, small-sized and positively charged amorphous calcium phosphate clusters allow minerals to penetrate into the gaps of collagen.
[0054] Step S1 specifically includes:
[0055] Dissolve polyacrylic acid in water, then add CaCl2 to obtain a mixed solution;
[0056] K2HPO4 solution was added dropwise to the mixed solution, and then NaOH was added to adjust the pH to 9.5±0.2 to obtain an amorphous calcium phosphate solution stabilized by polyacrylic acid.
[0057] In the present invention, the polyacrylic acid is first dissolved in water and then CaCl2 and K2HPO4 solutions are sequentially added to ensure that the polyacrylic acid is evenly distributed in the solution, which is beneficial for its uniform combination with calcium ions and phosphorus ions.
[0058] In the collagen solution, the concentration of collagen is 0.5-1 mg / mL, and the mass ratio of the collagen to the norepinephrine is 100:(0.5-5).
[0059] Preferably, the collagen comprises bovine collagen.
[0060] In the present invention, the above concentration range of collagen is conducive to the formation of anisotropy. Too high a concentration is likely to destroy the directional arrangement of collagen molecules, while too low a concentration is likely to result in a thinner thickness of the collagen film, which is not conducive to the subsequent step operation. The above concentration range of norepinephrine is limited by the properties of norepinephrine itself. Too high a concentration will produce negative effects, while too low a concentration will not be able to exert the desired effect.
[0061] Step S3 specifically includes:
[0062] The collagen solution is subjected to isoelectric focusing treatment for 10 to 20 minutes at a constant voltage of 10 to 20 V to form a dense membrane, and then the dense membrane is stretched at a speed of 1 to 3 mm / min to produce a deformation of 120% to 200%, thereby obtaining a collagen membrane with a bionic structure.
[0063] In the present invention, the voltage of isoelectric focusing treatment is 10-20V, which can efficiently prepare anisotropic collagen membrane while maintaining the material structure. Too high a voltage will cause a large number of bubbles to be generated, affecting the material structure, while too low a voltage will require more power-on time, affecting efficiency.
[0064] In the present invention, the dense membrane is stretched at a speed of 1 to 3 mm / min to produce a deformation of 120% to 200% in order to further improve the directional arrangement structure of the collagen molecules by stretching, while ensuring that during the mineralization process, the collagen molecules still maintain the anisotropic structure after forming collagen bundles.
[0065] Step S4 specifically includes:
[0066] The collagen membrane is immersed in the amorphous calcium phosphate solution at 37±1° C. for 12±2 hours, and then freeze-dried to obtain a norepinephrine-mineralized collagen scaffold material.
[0067] More specifically, the present invention provides a method for preparing a mineralized collagen scaffold material with a biomimetic structure, comprising:
[0068] (1) A polymer stabilization method was used to prepare an amorphous calcium phosphate solution. The specific method was as follows: prepare the raw materials of anhydrous CaCl2, K2HPO4·3H2O, and PAA, weigh 0.04-0.08 g of PAA and dissolve it in 40 ml of RO water, stir at room temperature for 15 min, add 0.222-0.888 g of anhydrous CaCl2 and continue to stir evenly; weigh 0.04-0.08 g of PAA and dissolve it in RO water, add K2HPO4 to prepare 40 ml of 0.03-0.12 M K2HPO4 solution, and slowly drip it into the above solution; after the addition was completed, continue to stir at room temperature for 30 min to mix it evenly, and the final solution Ca:P was 1.67; adjust the pH to 9.5±0.2 with NaOH.
[0069] (2) The preparation system of the mineralized collagen scaffold material with bionic structure is as follows: first, 13 mg / g collagen is added to RO water to dilute it into 0.5-1.0 mg / ml collagen solution, and 5-50 μl of 20 mg / ml norepinephrine solution is added and stirred for 30 minutes; a Ti sheet is used as an anode and a graphite sheet is used as a cathode, and a constant voltage of 10-20 V is applied to the above collagen solution through an electrochemical workstation for 10-20 minutes to obtain a dense collagen sheet with directional arrangement; the collagen sheet is stretched at a speed of 1-3 mm / min through a tensile texture analyzer to produce a tensile deformation of 120%-200%, thereby further improving the directional arrangement of the collagen fibers; finally, the material is immersed in a 0.025-0.1 M amorphous calcium phosphate solution at a constant temperature of 37±1°C for 12±2 hours, and the material is taken out and dried through a freeze dryer to obtain a mineralized collagen scaffold material with a bionic structure loaded with norepinephrine for the repair of bone defects.
[0070] The preparation method of a mineralized collagen scaffold material with a biomimetic structure, the mineralized collagen scaffold material and its application will be described in detail below in combination with examples and experimental data.
[0071] Example 1
[0072] The present embodiment provides a method for preparing a mineralized collagen scaffold material with a biomimetic structure, specifically comprising:
[0073] 1) A polymer stabilization method is used to prepare an amorphous calcium phosphate solution, and the specific method is as follows: prepare raw materials anhydrous CaCl2, K2HPO4·3H2O, and PAA, weigh 0.05g PAA and dissolve it in 40ml RO water, stir at room temperature for 15min, add 0.222g or 0.444g or 0.888g anhydrous CaCl2 and continue to stir evenly; weigh 0.05g PAA and dissolve it in RO water, add K2HPO4 to prepare 40ml of 0.03M or 0.06M or 0.12M K2HPO4 solution, and slowly drop it into the above solution; after the dropwise addition is completed, continue to stir at room temperature for 30min to mix evenly, and the final solution Ca:P is 1.67; adjust the pH to 9.5 with NaOH.
[0074] 2) The preparation system of the biomimetic structure mineralized collagen scaffold loaded with norepinephrine is as follows: first, 13 mg / g bovine collagen (extracted from bovine Achilles tendon - fresh bovine Achilles tendon with the aponeurosis, fat and muscle removed was cut into small pieces, soaked in 10% NaCl solution for about 24 hours, then washed with deionized water several times and dried naturally at room temperature. 50 g Achilles tendon was weighed and soaked in 0.5 M acetic acid solution for 2 hours, pepsin was added at a ratio of 1:50 between the mass ratio of enzyme and Achilles tendon, and enzymolysis was stirred at 4°C for 72 hours. The blocky solids were filtered out, the filtrate was refrigerated and centrifuged at 4000 rpm / min for 20 min, the supernatant was collected and salted out using 0.75 M NaCl solution, followed by dialyzation at 4°C for 3 days, and finally the concentration of collagen was determined using a freeze dryer) was added with RO water to dilute to 20 ml of 0.75 mg / ml collagen solution, and 20 μl was added. A 20 mg / ml norepinephrine solution was stirred for 30 minutes; a Ti sheet was used as an anode and a graphite sheet was used as a cathode, and a constant voltage of 15V was applied to the above collagen solution through an electrochemical workstation for 15 minutes to obtain a dense collagen sheet with directional arrangement; the collagen sheet was stretched at a speed of 2 mm / min through a tensile texture analyzer to produce a 150% tensile deformation, thereby further improving the directional arrangement of the collagen fibers; finally, the material was immersed in an amorphous calcium phosphate solution with a calcium ion concentration of 0.025 M, 0.05 M, and 0.1 M at a constant temperature of 37°C for 12 hours, and the material was taken out and dried by a freeze dryer to obtain an anisotropic mineralized collagen scaffold loaded with norepinephrine for the repair of bone defects.
[0075] Example 2
[0076] In this example, the performance of the scaffold material prepared in Example 1 was tested, as follows:
[0077] 1. The collagen, oriented collagen membrane and the prepared mineralized collagen scaffold sample in the preparation process of the norepinephrine-mineralized collagen scaffold in Example 1 were cut into cross sections along the oriented arrangement direction with a thin blade, fixed on the sample stage with double-sided conductive adhesive, and subjected to gold spraying for 90 seconds. The cross-sectional micromorphology was observed using a scanning electron microscope (SEM) at an accelerating voltage of 3.5 kV. The results are as follows: Figure 1 , Figure 1 EC represents the collagen membrane with biomimetic structure of the present invention, and ACP represents amorphous calcium phosphate. The preparation methods of EC+0.025MACP, EC+0.05MACP and EC+0.1MACP materials are as follows:
[0078] 1) Same as step 1) in Example 1;
[0079] 2) Norepinephrine solution was added to the collagen solution, and the remaining operations were the same as step 2) of Example 1 to obtain EC+0.025MACP, EC+0.05MACP and EC+0.1MACP materials.
[0080] like Figure 1 As shown in the figure, the amorphous collagen scaffold and the oriented collagen scaffold present a porous surface, while the other four lamellar scaffolds present multiple, interwoven long mineralized collagen fibers. The amorphous collagen scaffold is in a disordered state, and the arrangement of the collagen fibers is random and has no directionality. The collagen fibers in the collagen scaffold prepared by isoelectric focusing can be clearly seen to have a directional arrangement, and the basic D-band structure of the collagen can be more clearly seen compared to amorphous collagen. Comparing the morphology of the scaffold materials prepared by the three mineralization concentrations, it can be seen that the minerals cover the surface of the collagen fibers. It can be observed that under the mineralization conditions of EC+0.05MACP, the complete anisotropic structure can be retained under the condition of complete mineralization; the mineralization of EC+0.025MACP is incomplete; the morphology of the collagen fibers under the mineralization conditions of EC+0.1MACP is covered. At the same time, it can be observed through EC+0.05MACP+NE that the addition of NE did not change the surface morphology of the scaffold material.
[0081] 2. The mineralized collagen scaffolds with different mineralization conditions were prepared into sheets with a length of 2.5 cm, a width of 2.5 cm, and a thickness of 1 mm. They were fixed on the fixture of a universal mechanical testing machine and tested at a tensile rate of 2 mm / min. Stress-strain curves were drawn to characterize the tensile properties of the mineralized collagen scaffolds under different mineralization conditions. The results are shown in Figure 2. Figure 2 .
[0082] like Figure 2 As shown in the figure, the upper figure shows the experimental results of stretching along the oriented arrangement direction (longitudinal direction), and the lower figure shows the experimental results of stretching perpendicular to the oriented arrangement direction (transverse direction). It can be observed that different degrees of mineralization significantly change the mechanical properties of the material. The mechanical properties of the scaffold increase with the increase of the concentration of the mineralizing solution. The maximum tensile stress of the EC+0.1MACP material exceeds 2.5MPa. The presence of hydroxyapatite crystals enhances the stiffness of the collagen fibers, but also reduces its elastic deformation range, thereby reducing its fracture toughness. Affected by the arrangement direction of collagen fibers, the stiffness and toughness of the bionic structure collagen scaffold that has not been mineralized in the longitudinal stretching are better than those of the unoriented collagen scaffold under the same conditions; under the same conditions, the mechanical strength of the scaffold material in the transverse direction is significantly weaker than that in the longitudinal direction, and the stiffness and toughness in the transverse direction are lower than those in the longitudinal direction of the same group; compared with the unoriented collagen scaffold, the anisotropic scaffold has better mechanical properties in the longitudinal direction, but weaker mechanical properties in the transverse direction, proving that the material has anisotropy.
[0083] 3. Co-culture amorphous collagen, EC+0.05MACP and EC+0.05MACP+NE materials with BMSC cells. On the third day, remove the culture medium and add 110 μL of fresh culture medium containing cell counting reagent (Cell Counting Kit-8, CCK-8) (the ratio of CCK-8 detection solution to culture medium is 1:10). Determine the relative cell activity according to the procedure in the reagent manual. The results are as follows: Figure 3 .
[0084] like Figure 3 As shown in the figure, it can be seen that after collagen mineralization, there is no massive cell death, proving that the material has good biocompatibility. Comparing the materials with and without NE addition, it can be observed that the cell growth of the material with NE is better than that of the material without NE, indicating that the addition of NE is beneficial to cell growth.
[0085] 4. Anesthetize 8-week-old rats by intraperitoneal injection of 4% sodium pentobarbital (40 mg / kg). Skin the rat's head and clean the surgical site with iodine. Then make an incision near the sagittal midline to expose the parietal bone. Remove the pericranium and use a trephine to create a 5 mm defect on the side of the non-suture-related parietal bone to avoid perforation of the dura mater. Clean the surgical area with saline, and fill each defect with the prepared mineralized collagen scaffold. After implantation, suture the skin. Rats were killed by intraperitoneal injection of an overdose of sodium pentobarbital 28 days after surgery, and the skulls were obtained and preserved in 4% paraformaldehyde for Micro-Computed Tomography (μCT) evaluation.
[0086] like Figure 4As shown in the figure, it was observed that the skull of rats with biomimetic mineralized collagen scaffolds showed better repair effects, indicating that the implanted scaffold material has good in vivo biocompatibility. The new bone coverage of bone tissue generated by rats implanted with NE-loaded mineralized collagen scaffolds is larger. On the one hand, it is attributed to the repair effect of mineralized collagen on bone tissue defects and plays an important role in the process of bone formation; on the other hand, it may be attributed to NE promoting BMSCs to release neurotrophic factors, promote nerve regeneration, and cooperate with mineralized collagen to promote new bone formation.
[0087] Finally, it should be noted that the terms "comprises," "includes," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements that are inherent to such process, method, article, or apparatus.
[0088] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0089] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a mineralized collagen scaffold material with a biomimetic structure, characterized in that: The preparation method comprises: preparing an amorphous calcium phosphate solution stabilized by polyacrylic acid, wherein the molar ratio of the Ca element to the P element in the amorphous calcium phosphate solution is 1.67:1; Prepare a collagen solution containing norepinephrine; The collagen solution is subjected to isoelectric focusing treatment at a constant voltage to form a dense membrane, and then the dense membrane is stretched to produce a deformation of 120% to 200%, thereby obtaining a collagen membrane with a bionic structure; The collagen membrane is immersed in the amorphous calcium phosphate solution and then freeze-dried to obtain a norepinephrine-mineralized collagen scaffold material.
2. The method for preparing a mineralized collagen scaffold material with a biomimetic structure according to claim 1, characterized in that: In the amorphous calcium phosphate solution, the concentration of polyacrylic acid is 1-2 mg / mL, the concentration of calcium ions is 0.025-0.1 mol / L, and the concentration of phosphate ions is 0.015-0.06 mol / L.
3. The method for preparing a mineralized collagen scaffold material with a biomimetic structure according to claim 1 or 2, characterized in that: The preparation of the amorphous calcium phosphate solution stabilized by polyacrylic acid specifically comprises: Dissolve polyacrylic acid in water, then add CaCl2 to obtain a mixed solution; K2HPO4 solution was added dropwise to the mixed solution, and then NaOH was added to adjust the pH to 9.5±0.2 to obtain an amorphous calcium phosphate solution stabilized by polyacrylic acid.
4. The method for preparing a mineralized collagen scaffold material with a biomimetic structure according to claim 1, characterized in that: In the collagen solution, the concentration of collagen is 0.5-1 mg / mL, and the mass ratio of the collagen to the norepinephrine is 100:(0.5-5).
5. The method for preparing a mineralized collagen scaffold material with a biomimetic structure according to claim 1, characterized in that: The collagen includes any one of bovine collagen, porcine collagen and fish skin collagen.
6. The method for preparing a mineralized collagen scaffold material with a biomimetic structure according to claim 1, characterized in that: The step of subjecting the collagen solution to isoelectric focusing at a constant voltage to form a dense membrane, and then stretching the dense membrane to produce a 120% to 200% deformation to obtain a collagen membrane with a bionic structure specifically comprises: The collagen solution is subjected to isoelectric focusing treatment for 10 to 20 minutes at a constant voltage of 10 to 20 V to form a dense membrane, and then the dense membrane is stretched at a speed of 1 to 3 mm / min to produce a deformation of 120% to 200%, thereby obtaining a collagen membrane with a bionic structure.
7. The method for preparing a mineralized collagen scaffold material with a biomimetic structure according to claim 1, characterized in that: The step of soaking the collagen membrane in the amorphous calcium phosphate solution and then freeze-drying the solution to obtain a norepinephrine-mineralized collagen scaffold material specifically comprises: The collagen membrane is immersed in the amorphous calcium phosphate solution at 37±1° C. for 12±2 hours, and then freeze-dried to obtain a norepinephrine-mineralized collagen scaffold material.
8. A mineralized collagen scaffold material with a biomimetic structure, characterized in that: The mineralized collagen scaffold material is prepared by the method for preparing a mineralized collagen scaffold material with a biomimetic structure according to any one of claims 1 to 7.
9. Use of the mineralized collagen scaffold material with a bionic structure as claimed in claim 8 as or in the preparation of a bone defect repair material.
10. A bone defect repair material, characterized in that: The bone defect repair material comprises a mineralized collagen scaffold material with a biomimetic structure as claimed in claim 8; Alternatively, the raw material for preparing the bone defect repair material comprises the mineralized collagen scaffold material with a bionic structure as described in claim 8.
Citation Information
Patent Citations
Method for preparing bioactive poly(lactic-co-glycolic acid) / collagen / hydroxyapatite composite fiber membrane for bone repair
CN101791438A
Method for inducing bionic calcification in collagen fibers through polymer polyelectrolyte, and applications thereof
CN107224609A
Collagen membrane with highly oriented and crystalline collagen fiber structure and preparation method thereof
CN114618017A
Method and material for inducing biomimetic mineralization in collagenous fibers by hyaluronic acid and application of material
CN115227873A
Collagen composite membrane for guiding bone regeneration as well as preparation method and application of collagen composite membrane
CN117547659A
Cited By
Inorganic mineral and protein compounding method
CN120132054A
Directional multifunctional bone repair scaffold prepared by pulling-folding method and preparation method and application thereof
CN120514925A